Quest for the Spark. Book 1 - Sniegoski, Tom.; Smith, Jeff; Hamaker, Steve (New York : Scholastic, 2011)
Twelve-year-old Tom Elm, his raccoon friend Roderick, Percival, Abbey, and Barclay Bone, warrior priest Randolf, and forest woman Lorimar join in a quest to find the pieces of the Spark that can save Dreaming--and the Waking World--from a Darkness created by the Nacht.
"Graphix."
Keywords: Adventure and adventurers; Heroes; Dreams; Magic; Fantasy; Humorous stories